Epigenetic regulation of histone modifications in glioblastoma: recent advances and therapeutic insights - Li Zhang; Yang Yang; Yanchu Li; Chenyu Wang; Chenbin Bian; Hongbin Wang; Feng Wang (Biomarker Research)
Abstract Glioblastoma (GBM) is the most common primary malignant brain tumor, characterized by its aggressive behavior, limited treatment options, and poor prognosis. Despite advances in surgery, radiotherapy, and chemotherapy, the median survival of GBM patients remains disappointingly short. Recent studies have underscored the critical role of histone modifications in GBM malignant progression and therapy resistance. Histones, protein components of chromatin, undergo various modifications, including acetylation and methylation. These modifications significantly affect gene expression, thereby promoting tumorigenesis and resistance to therapy. Targeting histone modifications has emerged as a promising therapeutic approach. Numerous pre-clinical studies have evaluated histone modification agents in GBM, including histone deacetylase inhibitors and histone methyltransferase inhibitors. These studies demonstrate that modulating histone modifications can alter gene expression patterns, inhibit tumor growth, induce apoptosis, and sensitize tumor cells to conventional treatments. Some agents have advanced to clinical trials, aiming to translate preclinical efficacy into clinical benefit. However, clinical outcomes remain suboptimal, as many agents fail to significantly improve GBM patient prognosis. These challenges are attributed to the complexity of histone modification networks and the adaptive responses of the tumor microenvironment. This review provides a comprehensive overview of epigenetic regulation mechanisms involving histone modifications in GBM, covering their roles in tumor development, tumor microenvironment remodeling, and therapeutic resistance. Additionally, the review discusses current clinical trials targeting histone modifications in GBM, highlighting successes, limitations, and future perspectives.